2018
DOI: 10.3390/ma11071204
|View full text |Cite
|
Sign up to set email alerts
|

Anion Doping of Ferromagnetic Thin Films of La0.74Sr0.26MnO3−δ via Topochemical Fluorination

Abstract: Chemical doping via insertion of ions into the lattice of a host material is a key strategy to flexibly manipulate functionalities of materials. In this work, we present a novel case study on the topotactic insertion of fluoride ions into oxygen-deficient ferromagnetic thin films of La0.74Sr0.26MnO3−δ (LSMO) epitaxially grown onto single-crystal SrTiO3 (STO) substrates. The effect of fluorination on the film structure, composition, and magnetic properties is compared with the case of oxygen-deficient and fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…It was reported that the fluorination of bulk SrMnO 2.5 powders to Sr 2 Mn 2 O 5−x F 1+x resulted in the oxidation of Mn cations to a mixed Mn 3+ /Mn 4+ valence, which suggests F incorporation into O vacancies was the dominant mechanism [26]. Fluorination of epitaxial La 0.74 Sr 0.26 MnO 3−δ films was found to occur through a combination of F insertion of anion vacancies and substitution for O, resulting in a decrease of the Curie temperature [28]. Our recent study of fluorination mechanisms in epitaxial SrMnO 2.5 films revealed F substitution for O as the dominant means of fluorine incorporation.…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that the fluorination of bulk SrMnO 2.5 powders to Sr 2 Mn 2 O 5−x F 1+x resulted in the oxidation of Mn cations to a mixed Mn 3+ /Mn 4+ valence, which suggests F incorporation into O vacancies was the dominant mechanism [26]. Fluorination of epitaxial La 0.74 Sr 0.26 MnO 3−δ films was found to occur through a combination of F insertion of anion vacancies and substitution for O, resulting in a decrease of the Curie temperature [28]. Our recent study of fluorination mechanisms in epitaxial SrMnO 2.5 films revealed F substitution for O as the dominant means of fluorine incorporation.…”
Section: Introductionmentioning
confidence: 96%
“…Similar experimental results have also been reported in other studies. [37,38] As discussed above, the intrinsic oxygen chemical bonds also contribute a lot in achieving outstanding ORR/OER catalytic performance. Considering the importance of oxygen vacancies concentration in air electrode materials, thermogravimetric (TG) analysis was carried out to determine the oxygen nonstoichiometry (𝛿) of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…In future studies, we anticipate that this approach can be expanded to other material systems amenable to fluoridation, such as cobaltites, [ 66,67 ] manganites, [ 68–70 ] chromites, [ 71 ] nickelates, [ 72 ] and ruthenates. [ 73 ] While F is particularly useful for topochemical modification of the nature used here, it is also possible that other halides, pnictides, and chalcogenides could be used in a similar manner.…”
Section: Resultsmentioning
confidence: 99%